Atenuação passiva de um sistema rotativo utilizando lâminas de LMF superelásticas - Senko, Richard (2018)
The application of smart materials in rotor dynamics for the reduction of vibrations has been extensively studied since these being important for the industry. The most common application is to incorporate active elements called Shape Memory Alloy (SMA), which changes its micro structural characteristics with the alteration of temperature or mechanical stress. The SMAs has two characteristic behaviors: the memory effect (ME), which changes its phase due to temperature, and the superelasticity (SE), which modifies its phase with the mechanical stress. Nowadays the ME characteristic has been more used, which one requires an active control system for heating and cooling purposes and most often using elements in the form of helical springs. It is also noted that with the incorporation of this device, the natural frequencies of the system change, being evident that the reduction of the amplitudes of vibration is due to the variation of the stiffness of the material. The purpose of this work is to design and apply a blade of SMA SE type material that acts passively in a rotating system, mitigating the mechanical vibrations due to the passage through the natural frequencies using hysteretic damping of the material. For this, some conceptions were designed and simulations were performed with variations of the design parameters, in order to improve the vibration attenuation of the rotating system. After simulations, a type of device for manufacturing was selected and static and dynamic experimental tests were carried out to characterize the material. Finally, this device was incorporated into a support bearing of the rotary system and from the results obtained, it was compared to a system using an SMA ME helical springs. After the selection of the blade type spring of SMA SE, using simulations, as result of the application in the rotary system a reduction of up to 66% were achieved in relation to the system using SMA ME helical springs.